Board Features and Timely Disclosure of Audited Accounts of Listed Deposit Money Banks in Nigeria - Mailafia, Luka; Adamu, Jibril (Universitas Syiah Kuala, 2021)
ObjectiveThis study examines the moderating effect of company age on the relationship between board features on timely disclosure of audited financial statements. Specifically it tests the effects of board size, proportionate audit committee size, board independence on timely disclosure of the banks under study; and assess the influence of age as a moderator of board size, proportionate audit committee size, and board independence respectively as they affect timely disclosure of the listed deposit money banks in Nigeria.Design/methodologyThe sample of 10 banks out of 15 listed deposit money banks in Nigeria were used. Secondary data was gathered from the sampled banks annual accounts and reports. Correlational research design was used to examine the relationship between the studied variables. Descriptive statistics, correlation, and hierarchical multiple regression analyses were eventually carried.Results This study finds that board size and proportionate audit committee size are negatively related to timely disclosure of listed deposit money banks in Nigeria with the later exerting significant effect on the dependent variable. Furthermore, company age moderates both corporate governance and timely disclosure. Therefore, this study recommends that companies should strategize ways to improve corporate governance practice in order to inspire confidence on investors by timely disclosure of the financial report.Contribution The study has been able to provide evidence on age as a moderator to some corporate governance determinants of timeliness disclosure peculiar to Nigerian Deposit Money Banks. It has also addressed the measurement issue regarding audit committee size, introduced a new term known as proportionate audit committee size as a variable.